The Leaching of Manganese Ore from Patappa, Barru Regency, South Sulawesi - Nurhawaisyah, Sitti Ratmi; Jafar, Nurliah; Heriansyah, Andi Fahdli; Arifin, Mubdiana; Juradi, Muhammad Idris; Febrianty, Vanda; Utami, Hesti; Bakri, Suriyanto (Indonesian Journal of Chemical Research, 2025)
Manganese ores are considered economical and worth selling if they have a purity value above 40%. However, not all mined manganese metal minerals have the appropriate purity value. Manganese metal minerals can be processed using various hydrometallurgical methods to separate metal minerals from their associated minerals using solvents. The purpose of this study is to determine the results of manganese leaching recovery at each variation of temperature and percent solids and to determine the effect of both on manganese recovery. The findings of this study could significantly contribute to the field of metallurgy and mineral processing by providing a deeper understanding of the factors influencing manganese recovery. The method used in this study began with sample preparation. The results of sample preparation were analyzed using XRD (X-ray diffraction) and XRF (X-ray fluorescence). Some of the sample preparation results were leached with several variations in temperature; the leaching results were continued with analysis using AAS (Atomic Absorption Spectrophotometer). The results showed that increasing the leaching temperature and percent solids would increase the leaching reaction rate, resulting in higher Mn recovery.